"Attitudes and diffetrent practices related toabnormal vaginal discharge among women living in an estate community in Sri Lanka" - Ilankoon, I.M.P.S.; Gonewardena, C.S.E.; Fernandopulle, R.C.; Perera, P.P.R. (My University, 2016)
Vaginal discharge is known to cause distress, embarrassment and discomfort in women in reproductive age. This community based cross sectional study was aimed at describing the attitudes and different practices associated with vaginal discharge among females living in estate communities. Data were collected using a self-developed, validated, pretested interviewer-administered questionnaire. Descriptive statistics were used in analysis. A total of 550 women participated and the mean age was 33.8 (SD± 8.15) years. There were 36% Indian Tamils and 41.8% Sri Lankan Tamils. Nearly half of the population had primary education (n= 312, 56.7%). Majority (N=509, 92.5%) agreed that “it is necessary to take treatment for offensive vaginal discharge” indicating positive attitudes. Majority displayed negative attitudes towards health seeking namely “any type of vaginal discharge is a normal condition” (N= 429, 78%), “excessive vaginal discharge can occur due to body heat” (N= 411, 74.7%), “It is uncomfortable to talk about vaginal discharge” (N=262, 47.6%). Nearly half of them agreed that they have experienced vaginal discharge and only 30% of them have sought medical treatment. Main home remedies used were polpala herbal drink (31.3%), king coconut (34.7%) and sago (Sauw) kanji (26.0%). The reasons for not seeking medical advice were “difficulty in discussing with male doctors” (N=483, 87.8%), “less knowledgeable about vaginal discharge” (N=253, 46%) and “considering vaginal discharge as normal” (N=179, 32.5%). The findings implies the need of improving awareness and the available support system for this socially marginalized community in order to improve the health seeking behaviours towards excessive vaginal discharge.